2016
DOI: 10.1002/lary.25944
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative electromyographic characteristics of idiopathic unilateral vocal fold paralysis

Abstract: 4. Laryngoscope, 126:E362-E368, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…Husain et al showed that the time course of vocal recovery in IVFP follows a different pattern than that of iatrogenic vocal fold paralysis, with higher rates of recovery in the first 5 months in IVFP. Laryngeal electromyographic studies have shown that patients with IVFP have less severe denervation than those with vocal fold paralysis of known causes . Taken together, these data suggest that the pathophysiology of IVFP may be distinct from that of typical iatrogenic vocal fold paralysis.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Husain et al showed that the time course of vocal recovery in IVFP follows a different pattern than that of iatrogenic vocal fold paralysis, with higher rates of recovery in the first 5 months in IVFP. Laryngeal electromyographic studies have shown that patients with IVFP have less severe denervation than those with vocal fold paralysis of known causes . Taken together, these data suggest that the pathophysiology of IVFP may be distinct from that of typical iatrogenic vocal fold paralysis.…”
Section: Introductionmentioning
confidence: 85%
“…There is a much higher proportion of simultaneous involvement of the cricothyroid muscle (CT) with the laryngeal adductors in IVFP than in iatrogenic cases. In Chang et al, nine of 17 (53%) patients with IVFP had simultaneous RLN/superior laryngeal nerve (SLN) deficits based on quantitative laryngeal electromyography, whereas eight of 17 had only RLN deficit. In contrast, Only 24 of 107 (22%) patients with iatrogenic vocal fold paralysis had simultaneous RLN/SLN deficits.…”
Section: Discussionmentioning
confidence: 99%
“…The two‐stage model may not apply to this subset because it is unknown if there is a discrete site of dysfunction along the RLN. The degree of denervation based on quantitative LEMG is also less in idiopathic VFP compared to iatrogenic causes . Once the sample size of the idiopathic subset is sufficiently large, dedicated modeling of this group will be performed to see if the kinetics of recovery from idiopathic UVFP are distinguishable from iatrogenic UVFP.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, idiopathic UVFP has been a focus of research. Most cases of NSUVFP are idiopathic and have unique disease presentations . Idiopathic UVFP is defined as UVFP with unknown causes; however, previous studies have shown inconsistent results regarding the clinical presentation and long‐term prognosis for patients with idiopathic UVFP.…”
Section: Introductionmentioning
confidence: 99%